Development of Blind Walk Game Media to Train Students’ Interpersonal Communication Skills - Nuri Maulida; Ahmad Syarqawi (Journal of Social Work and Science Education, 2027)
Junior high school students often experience interpersonal communication difficulties, including expressing opinions, building trust, listening actively, and cooperating with peers. This study aimed to develop and assess a Blind Walk game-based medium for group guidance services designed to train students’ interpersonal communication skills. The study employed a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. However, the development process was limited to the Develop stage. The participants were eight eighth-grade students from SMP Swasta Cerdas Murni. Data were collected through interviews and questionnaires using media and material expert validation sheets, a guidance counselor response questionnaire, and a student response questionnaire. The media expert awarded a score of 80%, categorized as valid, while the material expert awarded 90%, categorized as very valid. Practicality scores reached 94% from the guidance counselor and 96.5% from the students, both categorized as very practical. The product was designed to facilitate cooperation, trust-building, clear instruction delivery, and active listening during group guidance activities. These findings indicate that the developed medium is valid and practical for limited use. Further experimental research is required to determine its effectiveness in improving interpersonal communication skills.